HUBUNGAN KUALITAS PENYELENGGARAAN MAKANAN DENGAN KEPUASAN PASIEN DI PELAYANAN GIZI RUMAH SAKIT MUHAMAMDIYAH KALITIDU - Firdaus, Desiana; Fithri, Istiqlal; Safitri, Ludviana Dwi; Andika, Hubi Rahmat (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Hospitals have several installations with different working systems, one of which is the nutrition installation. The success of a nutritional installation can be seen from patient satisfaction with the quality of the food service. Food management includes the accuracy of food presentation, the accuracy of food taste, and food waste. This study aims to determine the relationship between the quality of food service and patient satisfaction at the nutrition installation at the Muhammadiyah Kalitidu Hospital. The research design used was descriptive analytic with a cross sectional approach. Sample selection used incidental sampling technique and obtained a total of 91 samples of inpatients. Data on the quality of food service and patient satisfaction levels were obtained using the interview method using a questionnaire consisting of 11 questions for each variable. The bivariate test results show that there is a significant relationship between the quality of service and patient satisfaction at the Kalitidu Muhammadiyah Hospital nutrition installation as indicated by the p-value: 0.000 (<0.05) and a correlation coefficient of 0.506. This shows that the better the quality of food service, the more satisfied patients are with the nutritional installation at Kalitidu Muhammadiyah Hospital.